2019
DOI: 10.3389/fimmu.2019.00121
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Innate and Adaptive Immune Responses in a Cohort of Intractable Pediatric Epilepsy Surgery Patients

Abstract: Brain-infiltrating lymphocytes (BILs) were isolated from resected brain tissue from 10 pediatric epilepsy patients who had undergone surgery for Hemimegalencephaly (HME) (n = 1), Tuberous sclerosis complex (TSC) (n = 2), Focal cortical dysplasia (FCD) (n = 4), and Rasmussen encephalitis (RE) (n = 3). Peripheral blood mononuclear cells (PBMCs) were also isolated from blood collected at the time of the surgery. Cells were immunostained with a panel of 20 antibody markers, and analyzed by mass cytometry. To ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…More recently Xu et al reported that immune cells isolated from resected brain tissue from pediatric epilepsy surgeries comprised antigen experienced CD4, CD8 and Th17 gd T cells (10). In agreement with these observations, we also found that effector memory T cells are present in brain tissue that has been removed to treat seizures associated with cortical malformations including FCD, TSC and HME (11). By mass cytometry approximately half of the CD8 ab T cells that we isolated from FCD (n=4), TSC (n=2) and HME (n=1) surgery cases expressed CD69 (11), an activation marker (12).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…More recently Xu et al reported that immune cells isolated from resected brain tissue from pediatric epilepsy surgeries comprised antigen experienced CD4, CD8 and Th17 gd T cells (10). In agreement with these observations, we also found that effector memory T cells are present in brain tissue that has been removed to treat seizures associated with cortical malformations including FCD, TSC and HME (11). By mass cytometry approximately half of the CD8 ab T cells that we isolated from FCD (n=4), TSC (n=2) and HME (n=1) surgery cases expressed CD69 (11), an activation marker (12).…”
Section: Introductionsupporting
confidence: 92%
“…In agreement with these observations, we also found that effector memory T cells are present in brain tissue that has been removed to treat seizures associated with cortical malformations including FCD, TSC and HME (11). By mass cytometry approximately half of the CD8 ab T cells that we isolated from FCD (n=4), TSC (n=2) and HME (n=1) surgery cases expressed CD69 (11), an activation marker (12). In the TSC and FCD cases, the ab T cells isolated from the resected brain tissue comprised only a fraction of the brain-infiltrating leukocytes (BILs) ranging from 3.2% to 15.1%; the remaining cells were either gd T cells, natural killer (NK) or myeloid cells (11).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Neutrophils number have been shown to increase in the circulation as well as the CNS after a TBI [216], where they can influence cells of the adaptive immune system including CD8+ T cells, regulatory T cells, and CD4+ T helper cells [217]. Although to a lesser extent compared to neutrophils and monocytes/macrophages, T cells also infiltrate the injured and epileptic brain, where they contribute to ongoing neuropathology and disease severity [218,219,220]. An important role for peripheral adaptive immune cells has been suggested by experimental depletion of regulatory T cells in an epilepsy model, which resulted in increased seizures [219].…”
Section: Neuroinflammatory Mechanisms Driving Ptementioning
confidence: 99%
“…In human pediatric epilepsy, activated peripheral immune cells were reported in epileptogenic brain areas [ 11 ]. Among these, γδ T cells have been recognized as a component of brain infiltrating lymphocytes in pediatric epilepsy and in Rasmussen encephalopathy [ 11 , 12 ]. γδ T cells are a major subset of CD3+ T cells that line the gut epithelium and contribute to intestinal tissue homeostasis, repair and inflammation.…”
Section: Introductionmentioning
confidence: 99%